A study to assess the level of resilience and quality of life among patients with diabetes mellitus at selected villages under Rural Health and Training Centre - poongdi R; Sumathi M; Jothi J; Hasika N; Kavitha Ramanathan; Shenbagsundram Subramanian; Fadwa Alhalaiqa; Ghonan Samhan; Layla Abdelhadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disease with the clinical feature of an abnormally high blood glucose level, and it is considered a metabolic syndrome. Non-insulin Type 2 Diabetes Mellitus (NIDDM) is a chronic condition that significantly hampers patients' resilience and Activities of Daily Living (ADL), leading to a notable impact on their Quality of Life (QoL).